Penerapan Metode PQRST Dalam Pembelajaran Membaca Teks Anekdot Pada Siswa Kelas X SMAN 11 Pinrang - Wahyuna Amala T.A, Nurul; Rabiah, Sitti; Puspitasari, Andi (Educatio, 2023)
This research aims to determine the improvement in learning to read anecdotal texts using the PQRST (Preview, Question, Read, Summerize, Test) method for class X IPS 2 students at SMAN 11 Pinrang. This research is classroom action research (PTK), using the Kemmis and Taggart model. The data for this research are observation sheets and test sheets sourced from 22 students of class X IPS 2 SMAN 11 Pinrang. In the research, this was obtained based on observations of activities and the results of students' assignment scores in learning to read anecdotal texts. The data analysis techniques used are qualitative and quantitative. Based on the results of pre-cycle data analysis, the average score was 59, while in cycle I it was found that the results of observations of student learning activities obtained an active achievement of 79%, while in cycle II the student's active achievement was 88%. The result of learning to read anecdotal texts using the PQRST method in cycle I obtained an average score of 64%. Cycle II in the observation activities of meeting 1 showed that student activity in cycle I obtained an achievement of 98%, while in meeting 2 they obtained an achievement of 98%, while the value of learning results from reading anecdote texts in cycle II obtained an average of 78%. Therefore, it can be concluded that The application of the PQRST method in learning to read anecdotal texts in class X SMAN 11 Pinrang improves student learning outcomes in class.Keywords: PQRST method (Preview, Question, Read, Summerize, Test), Reading Anecdotal TextPenelitian ini bertujuan untuk mengetahui peningkatan pembelajaran membaca teks anekdot menggunakan metode PQRST (Preview, Question, Read, Summerize, Test) siswa kelas X IPS 2 SMAN 11 Pinrang. Penelitian ini adalah penelitian tindakan kelas (PTK), menggunakan model Kemmis and Taggart. Data penelitian ini adalalah lembar observasi dan lembar tes yang bersumber dari siswa kelas X IPS 2 SMAN 11 Pinrang yang berjumlah 22 orang. Dalam penelitian di peroleh berdasarkan observasi aktifitas dan hasil nilai tugas siswa dalam pembelajaran membaca teks anekdot. Teknik analisis data yang digunakan adalah kualitatif dan kuantitatif. Berdasarkan hasil analisis data pra-siklus memperoleh nilai rata-rata yaitu 59, sedangkan pada siklus I diketahui hasil observasi aktifitas belajar siswa memperoleh prestasi keaktifan yaitu 79%, sedangkan pada siklus II prestasi keaktifan siswa yaitu 88%. Nilai hasil pembelajaran membaca teks anekdot menggunakan metode PQRST siklus I memperoleh nilai rata-rata 64%. Siklus II pada kegiatan observasi pertemuan 1 menunjukkan bahwa keaktifan siswa pada pertemuan 1 memperoleh prestasi 97%, sedangkan pada pertemuan 2 memperoleh prestasi 98%, sedangkan nilai hasil pembelajaran membaca teks anekdot siklus II memperoleh hasil rata-rata 78%. Oleh karena itu, dapat di simpulkan bahwa penerapan metode PQRST dalam pembelajara membaca teks anekdot pada siswa kelas X SMAN 11 Pinrang meningkatkan hasil belajar siswa di kelas X IPS 2 SMAN 11 Pinrang.Kata kunci:Metode PQRST (Preview, Question, Read, Summerize, Test), Membaca Teks Anekdot